If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) = 3(x + -1) Reorder the terms: 2(-4 + x) = 3(x + -1) (-4 * 2 + x * 2) = 3(x + -1) (-8 + 2x) = 3(x + -1) Reorder the terms: -8 + 2x = 3(-1 + x) -8 + 2x = (-1 * 3 + x * 3) -8 + 2x = (-3 + 3x) Solving -8 + 2x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + 2x + -3x = -3 + 3x + -3x Combine like terms: 2x + -3x = -1x -8 + -1x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + -1x = -3 + 0 -8 + -1x = -3 Add '8' to each side of the equation. -8 + 8 + -1x = -3 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = -3 + 8 -1x = -3 + 8 Combine like terms: -3 + 8 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 2a-4=10a | | 5a+3+6a-12+90=180 | | 11-5=5 | | .7(200-x)=126 | | 7(y+4)=3y-8 | | x+50=180 | | 8[4-(-4x-9)]=64x+176 | | .7(200-x)=133 | | solve(2+4)(2-2)=-5 | | 3(12-5)^2/(4+3) | | -2.1q-1=6.6 | | -4U+3/2=7/2U-1/5 | | 4+2x+15=x+13 | | 12x+25=29 | | 5a+3+6a-12=180 | | 4.7+3g=7.3 | | sqrt(5-x)+1=x-2 | | 4.2(x+8.7)=8.7x | | -4-n-4=-11 | | 6-x=37 | | 12x-1+3=7x+1 | | 3a/2+1=18 | | 22/5d*10/2 | | 3-4q=10+10 | | 3a+6+4a=-36 | | x+11=2x-7 | | 5-9/2d=33 | | m/3=28 | | -4(k+3)-k-7=-5(k+5)+6 | | x+13+3=2x+16 | | 1/2t+9=4 | | -[10z(19z+3)]=3+(8z+10) |